Susceptibility Pattern of Salmonella Typhi in Culture Proven Enteric Fever in Children - Muhammad Zabih Ullah; Jan, Muhammad Shahan; Haji Gul; Ahmad, Waqar; Muhammad Rizwan; Ali, Ikram (Indus Journal of Bioscience Research, 2025)
Background: Enteric fever, primarily caused by Salmonella Typhi, remains a significant public health challenge, particularly among children. The World Health Organization estimates 11 to 20 million cases annually, with over 100,000 deaths. Children aged 1 to 5 years are especially vulnerable, with seasonal peaks observed during spring. Rising antibiotic resistance, including multidrug-resistant (MDR) and extensively drug-resistant (XDR) strains, complicates treatment and increases morbidity and mortality. Methods: A prospective analysis of 160 blood culture samples from paediatric patients at MTI-GKMC/BKMC Swabi was conducted. The study aimed to assess antibiotic resistance prevalence among S. Typhi isolates. Blood samples were cultured using standard microbiological methods, and susceptibility was determined via disk diffusion and minimum inhibitory concentration (MIC) testing against antibiotics such as azithromycin, meropenem, and imipenem. Results: Of the 160 positive samples, 136 (85%) exhibited extensive drug resistance (XDR), while 24 (15%) were classified as multi-drug resistant (MDR). All isolates remained sensitive to azithromycin, meropenem, and imipenem, suggesting these as viable treatment options despite widespread resistance. Conclusion: The study highlights the alarming prevalence of antibiotic resistance in paediatric enteric fever cases, particularly the high proportion of XDR strains. Continuous surveillance, judicious antibiotic use, and stringent infection control measures are essential to mitigate the spread of resistant strains. Public health interventions, including improved sanitation, vaccination programs, and targeted therapeutic strategies, are critical to reducing the burden of enteric fever in vulnerable populations.